The Roots and Uses of Marketing Knowledge a Critical Inquiry into the Theory and Practice of Marketing - Smith, Terry (De Gruyter, 2020)
Marketing theory is often developed in isolation not collaboration; theoretical perspectives sometimes are ignorant of the diversity of marketing practice. In "The roots and uses of marketing knowledge: a critical inquiry into the theory and practice of marketing", the author engages with the vital conversation about how marketing knowledge is created, disseminated and consumed, looking beyond the traditional reification of practice in theory and verification of theory in practice. The ontology of this work is anchored in subjective individual meaning; the epistemological stance assumes that this meaning is socially constructed. Consequently, rich empirical data, grounded in the context of experiential evidence, is extracted from a comprehensive range of marketing constituencies: academics, practitioners, managers, consultants, authors, lecturers and students. In its examination of the polarities, hybridity and iterative flow of marketing knowledge creation and consumption, this text posits a cohesive argument for a theory/practice bipartite fusion not dichotomy, adding valuable insights into the textual, contextual and pedagogical representations of marketing knowledge. The history and future of marketing knowledge is examined with the aid of instructive illustrations and insightful first-hand experience. Drawing on extensive qualitative research from a broad range of influential producers and vital consumers, Dr. Smith presents a relevant, exciting marketing knowledge framework which will be a vital resource for academics, students and practitioners.